Effect of Sintering Temperature on Formation of Gd0,95La0,05Ba1,95Sr0,05Cu3O7-d Compounds - Jeni, Asni Mulyati; Sumadiyasa, Made; Suryatika, Ida Bagus Made (BULETIN FISIKA, 2021)
Research has been conducted variations in sintering temperature between 900 ºC – 950 ºC for 12 hours on the synthesis phase of Gd 1 Ba 2 Cu 3 O 7- d   substituted La and Sr with stoichiometric composition Gd 0,95 La 0,05 Ba 1,95 Sr 0,05 Cu 3 O 7- d .  This study is intended to find out at what temperature the compound Gd 0,95 La 0,05 Ba 1,95 Sr 0,05 Cu 3 O 7- d     can be formed to the maximum. Samples with composition Gd 0,95 La 0,05 Ba 1,95 Sr 0,05 Cu 3 O 7- d  made from the raw materials Gd 2 O 3 , La 2 O 3 , BaO, Sr 2 O 3 and CuO . Samples are synthesized using solid-state reaction method by wet mixing with nitric acid (HNO 3 ) as solvent. The sample is sintering in the form of pellets in the furnace without annealing of oxygen gas. The synthesis results were characterized by X-Ray Diffraction (XRD) and analyzed with the Match-3 Program. By using the Entry number 96-153-9606, the results of it analysis showed that sintering temperature had an impact on the formation of phase compounds Gd 0,95 La 0,05 Ba 1,95 Sr 0,05 Cu 3 O 7- d . Show that the volume fraction is increases with increasing of the sintering temperature, especially from temperatures of 930 ºC to 950 ºC. The highest volume fraction of 75,4263 % was obtained in samples that sintering at 950 ºC. Refinement results with Rietveld analysis method showed phase Gd 0,95 La 0,05 Ba 1,95 Sr 0,05 Cu 3 O 7- d  formed is in orthorhombic symmetry. The volume of cell units is likely to increase as the temperature increases.